2018
DOI: 10.1080/00365521.2018.1445774
|View full text |Cite
|
Sign up to set email alerts
|

Patient radiation dose and fluoroscopy time during ERCP: a single-center, retrospective study of influencing factors

Abstract: Multiple factors had an effect on DAP and FT in ERCP. The awareness of these factors may help to predict possible prolonged procedures causing a higher radiation dose to the patient and thus facilitate the use of appropriate precautions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
3
11
0
Order By: Relevance
“…The higher effective dose difference of 58% was found applying the DAP reported by Saukko et al (2018), however the value estimated in this work was in agreement with the reported E values range of 0.02 to 3.69 mSv. The authors studied the data from 638 procedures performed between 2013 and 2015 for different patient complexity.…”
Section: Evaluation Of Patient Exposuresupporting
confidence: 91%
See 1 more Smart Citation
“…The higher effective dose difference of 58% was found applying the DAP reported by Saukko et al (2018), however the value estimated in this work was in agreement with the reported E values range of 0.02 to 3.69 mSv. The authors studied the data from 638 procedures performed between 2013 and 2015 for different patient complexity.…”
Section: Evaluation Of Patient Exposuresupporting
confidence: 91%
“…12.4 7.4 Saukko et al (2018) 2.33 0.61 (0.02-3.69) 0.3 Liao et al (2015) 13.98 3.63 (2.28-6.00) 1.5 8.8…”
Section: Evaluation Of Patient Exposurementioning
confidence: 99%
“…The extent of radiation exposure among medical staff is influenced by various factors, such as the environment of the endoscopy unit, distance between the medical staff and radiation source or patient, type of X-ray system (over-couch, under-couch, or mobile C-arm unit), fluoroscopy parameters (use of pulsed rather than continuous fluoroscopy, use of lower frame rates of fluoroscopy, number of radiographs, use of X-ray beam collimation, or use of low magnification), and use of protective equipment. [ 10 , 21 24 ] Moreover, the fluoroscopy time is influenced by various factors, such as the difficulty of the procedure, [ 25 , 26 ] proficiency levels of the endoscopist and assistant, [ 6 ] education and awareness of radiation protection, [ 27 , 28 ] and number of interventional endoscopic procedures during a specific period. Our institution uses an over-couch X-ray system associated with high radiation exposure at the endoscopist's thyroid gland and eye levels, and the dose might exceed the ICRP limit.…”
Section: Discussionmentioning
confidence: 99%
“…The physical environment of the ERCP unit, the distance between medical staff and the radiation source or the patient, the type of X-ray system (over-couch, under-couch, or mobile C-arm unit), the fluoroscopy parameters (use of pulsed rather than continuous fluoroscopy, use of lower frame rates of fluoroscopy, number of radiographs, use of collimation of X-ray beam, use of low magnification) and the use of protective equipment can affect the radiation dose 6 16–19. Moreover, the fluoroscopy time is determined by important factors such as the difficulty of the procedure,20 21 the proficiency level of the endoscopist and the assistant,22 education and awareness regarding radiation protection,23 24 and the number of ERCP procedures during the period. Hence, the different scenarios at each institution and those of the ERCP units should be taken into account when comparing the degree of radiation exposure for each institution.…”
Section: Discussionmentioning
confidence: 99%